Effect of Salary, Work Motivation and Work Discipline on the Performance of Bangil Religious Court Office Employees - Sakinah Fiqih Firdausi; Hasan Ubaidillah (Indonesian Journal of Islamic Studies, 2022)
This study aims to determine the effect of salary, work motivation, and work discipline on employee performance at the Bangil Religious Court office. This research includes quantitative research with hypothesis testing. The sample used in this study were 40 employees at the Bangil Religious Court office. The analytical tool used in this research is multiple linear regression analysis, determinant coefficient (R2), multiple correlation coefficient (R), f test, t test, and classical assumption test using SPSS. The primary data in this study were obtained from questionnaires whose measurements used a Likert scale which were tested for validity and reliability. The result of this research is that there is a simultaneous influence between salary, work motivation, and work discipline on employee performance. Partially, the variables of salary, work motivation and work discipline have an influence on employee performance. And work discipline is a variable that has the most significant influence on employee performance.